The new breaststroke turn - McCauley, W.
New rule changes for breaststroke and butterfly effective March 8th 1998, bring big changes to how we do our turns. The turn for butterfly is exactly the same as breaststroke. The turn and underwater stroke can account for up to 45% of a 200 short course breaststroke race; often the race is decided by whom does them best. We first now can put our head underwater without being disqualified, second the new streamline that has the arms behind the head, with the head squeezed in, allows much longer and farther underwater strokes and third the shoulders shall be no longer in line with the water surface. Author breaks down the present "open" breaststroke turn into five parts, which he explains in the article: - The Approach - The Turn - The Push Off - The Underwater Pull-Down - The First Stroke Up